Students' Self-Confidence in Islamic Religious Education Subject: An Experimentation of the Assure Learning Model - Nur Afifah; Nalita Azzura; Kurnia Khoirun Nisa; Muhammad Idri Utama; Muhammad Alif Akbar; Nurul Azizah (PT. Pusmedia Group Indonesia, 2025)
This study is grounded in the issue of low student self-confidence in Islamic Religious Education (PAI) learning at SMAN 12 Bandar Lampung, attributed to the continued use of conventional teaching methods and the limited integration of media and technology.The aim of this study is to examine the influence of the ASSURE learning model on the enhancement of students' self-confidence in the Islamic Religious Education subject. The research adopts a quantitative approach with a quasi-experimental design, specifically utilizing a post-test only control group design. The research sample was selected using simple random sampling from Grade X students, divided into two groups: an experimental class utilizing the ASSURE learning model and a control class using conventional teaching methods. The research instrument was a self-confidence questionnaire that had been validated and tested for reliability. The data analysis techniques included tests of normality, homogeneity, and hypothesis testing using the Independent Samples T-Test. The analysis results indicated a significant difference between the two groups, with a significance value of 0.048 (< 0.05), suggesting that the ASSURE model is effective in improving students' self-confidence. The ASSURE model, which is systematic, interactive, and technology-based, has proven effective in creating an active and enjoyable learning environment, while also enhancing students' self-confidence in expressing opinions, making decisions, and facing challenges. This study suggests that teachers should be more creative in selecting instructional models and encourages the use of technology to enhance the quality of Islamic Religious Education.